Pengaruh Trend Komunikasi Virtual terhadap Kemahiran Komunikasi Interpersonal mahasiswa IUQI Bogor - Saoqillah, Akhmad; Fitiya, Wilda; Lutfiatunnisa, Siti (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2023)
Students at the Ummul Quro Al Islami Bogor Institute are currently more familiar and many even use virtual communication in their daily lives on campus, this is in line with the increasingly rapid growth of virtualcommunication platforms such as WhatsApp and the like, so this influences conversations in the real world. The aim of this research is to find out how the virtual communication trend influences students' interpersonal communication skills. This research uses quantitative research methods. The research subjects were students of the Ummul Quro Institute from 9 existing study programs, namely KPI, BKI, MPI, PBA and others. The results of the research were related to an increase in the effectiveness of virtual communication but a decrease in interpersonal communication interactions. The main factor that is felt to be hindering is that the trend of virtual communication has not yet become more rapid so that students forget their identity in the real world due to their busy lives in the virtual world.